HUBUNGAN ANTARA PEMAHAMAN UNSUR KEBAHASAAN DAN SIKAP TERHADAP BAHASA INDONESIA DENGAN KOMPETENSI MENULIS KARYA ILMIAH MAHASISWA - Rian Apriliani (Kajian Linguistik dan Sastra, 2016)
This study aims at investigating the presence of correlation between comprehension of language elements and attitude towards Indonesian language with scientific paper writing competence. This research was conducted on the students of MIPA-FKIP UNS from July to November 2015 by employing survey method as a tool of correlational study. The population included all students of PMIPA-FKIP UNS attending Indonesian language course and the research samples were 70 students, gathered using cluster random sampling technique. The research data were collected with composition test of scientific paper writing, test of comprehension of language elements and questionnaires on attitude towards Indonesian language. Afterwards, the data were statistically analyzed using simple and multiple regression analyses and correlation analysis. The researchresults indicate that 1) there is a positive and significant correlation between comprehension of language elements and scientific paper writing competence; 2) there is a positive and significant correlation between attitude towards Indonesian language and scientific paper writing competence; and 3) there is a positive and significant correlation between comprehension of language el ements and attitude towards Indonesian language along with scientific paper writing competence.